Pengukuran Pengaruh Kualitas Layanan Aplikasi UNMER Malang Digital Library Menggunakan Metode SERVQUAL - Ningsih, Yulia Widya (Universitas Multi Data Palembang, 2024)
The implementation of technology into the service system helps to improve the quality of services provided, Merdeka University Library Malang implements this technology into the UNMER MALANG Digital Library application service which is a book lending service and library information media, changes in services that were once conventional into digital services are expected to improve the quality of services in the library, using the servqual method this study measures the extent to which the quality of the UNMER MALANG Digital Library application services meets the needs of its users. Each variable of the application system service measured will produce a gap value between user perceptions received and user expectations that will be received in using this application. The data used in this study are questionnaire data processed using SPSS which is then analyzed by applying the Servqual method. This study shows that each variable dimension applied tangible, reliability, responsiveness, empathy, and assurance shows a positive influence value in user satisfaction and improving the quality of system services must be further improved in order to make services more effective and efficient.